Not Always a Thymoma – About a Mediastinal Cavernous Hemangioma - Pinto, Paula (2023)
A mediastinal cavernous hemangioma is difficult to distinguish from other types of mediastinal tumours. They are usually asymptomatic and incidentally discovered in an imaging study but can present with compressive symptoms or by infiltration of adjacent structures. A 64-year-old woman with a prior history of triple negative invasive carcinoma of the breast, under surveillance was referred after a Chest CT-scan showed a soft tissue 40x20 mm mediastinal mass, suggestive of a thymoma, and as such no tissue biopsy was obtained. A right-side uniportal VATS was performed, the anterior mediastinum dissected and the mass was exposed, and several anomalous veins were identified. Histopathology showed 36x31x15 mm mass, compatible with a cavernous hemangioma of the anterior mediastinum. This case, whilst not questioning the NCCN statement suggesting not doing a tissue biopsy, points to the fact that rare differential diagnosis, like a Cavernous Hemangioma do exist, and a careful and sound judgement is needed at all times.